The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1098/rspb.2011.0958
|View full text |Cite
|
Sign up to set email alerts
|

Host behaviour and physiology underpin individual variation in avian influenza virus infection in migratory Bewick's swans

Abstract: Individual variation in infection modulates both the dynamics of pathogens and their impact on host populations. It is therefore crucial to identify differential patterns of infection and understand the mechanisms responsible. Yet our understanding of infection heterogeneity in wildlife is limited, even for important zoonotic host-pathogen systems, owing to the intractability of host status prior to infection. Using novel applications of stable isotope ecology and eco-immunology, we distinguish antecedent beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 46 publications
6
36
0
1
Order By: Relevance
“…Although a potentially extreme example, such cases highlight the imperative to better understand the role of migration in modulating disease dynamics, particularly factors influencing individual susceptibility to infection, behavioural alterations as a result of infection and how such changes in behaviour will influence transmission. There is some evidence that susceptibility to infection may differ between individuals on the basis of age and infection history [54], and throughout the annual cycle. There is, however, no comprehensive understanding of the mechanisms constraining resistance and tolerance to infection among individuals.…”
Section: Reductions In Habitat Quality (A) Diseasementioning
confidence: 99%
“…Although a potentially extreme example, such cases highlight the imperative to better understand the role of migration in modulating disease dynamics, particularly factors influencing individual susceptibility to infection, behavioural alterations as a result of infection and how such changes in behaviour will influence transmission. There is some evidence that susceptibility to infection may differ between individuals on the basis of age and infection history [54], and throughout the annual cycle. There is, however, no comprehensive understanding of the mechanisms constraining resistance and tolerance to infection among individuals.…”
Section: Reductions In Habitat Quality (A) Diseasementioning
confidence: 99%
“…Hoye, Fouchier, and Klaassen [8], and references therein, suggest that host age is one of various factors that influence susceptibility to avian influenza infection. In that paper, it is suggested that juvenile Bewick's swans (Cygnus columbianus bewickii) are more likely than adults to be infected with avian influenza viruses (30.8%, compared to 11.3% for adults), shed approximately 15 times as many viruses as adults do, and exhibit a lower specific immune response than adults.…”
Section: Nonmigratory Speciesmentioning
confidence: 97%
“…Webster et al [20] also report extensive evidence for movement of avian influenza viruses or their genes between wild ducks and other species including other wild birds, pigs, horses, and some marine mammals, and possibly humans, and this further suggests consideration of the The model formulation is complicated, and therefore we begin by developing an age structured SIR (susceptible-infectious-recovered) model for a nonmigratory bird species. We emphasize the importance of age dependence from the outset because of the availability of evidence (see, for example, Hoye, Fouchier, and Klaassen [8] and the references therein) suggesting that host age influences susceptibility to avian influenza infection. We begin with age-structured equations that are reformulated as a system of seven delay differential equations for the total numbers of juvenile and adult susceptible, infectious, and recovered birds and the number of viruses.…”
Section: Introductionmentioning
confidence: 98%
“…For example, energetic budgets, oxygen consumption and hormonal actions are physiological changes related to the age and body size of the organism (Wilmer et al 2006). In addition, these physiological characteristics are associated with animal behavior, such as distribution, displacement, diet and habitat preferences (Restif et al 2001), which are factors that can influence parasite transmission and infection of the hosts (e.g., Møller and Rózsa 2005;Hoye et al 2012).…”
Section: Discussionmentioning
confidence: 99%